PROTAGONIST ATTITUDE OF CARE PROVIDERS IN ESCALATING THE RATES OF CAESAREAN SECTION - Baig, Jehan Ara Rafiq; Khalil, Adiba Akhtar; Baqai, Shehla; Choudry, Abeera; Siraj, Asifa; Jannat, Munnawar; Tariq, Humaira (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess obstetrical care providers‟ delivery preferences and perceptions along with attitude towards caesarean section on maternal request and the possible effect of providers‟ characteristics on decision making. Study Design: Cross-sectional study. Place and Duration of Study: Study was done in five hospitals, from 1st Aug to 31st Aug 2019. Methodology: Obstetrical Care providers in hospitals with at least 4000 births per year completed a self-administered, anonymous questionnaire. Delivery preferences and perceptions about low-risk women, opinion about a woman‟s right to choose her delivery method and the willingness to perform caesarean section on maternal request were assessed. Results: Out of 109 participants, 105 (96.3%) preferred a vaginal delivery for their patients in the absence of a medical indication for caesarean section. Majority 74 (67.8%) believed patients should be permitted to choose their mode of delivery, while 85 (78%) were willing to perform caesarean section on maternal request. There was significant association between perceptions and the mode of delivery. More responders were willing for caesarean section on maternal request who were less than 35 years of age, had no biological children or had less than 4, who had had vaginal deliveries themselves, were trainee doctors or who had less than 10 years of obstetrical consultant experience. These associations were not statistically significant. Conclusion: Our study revealed strong association between perceptions and personal beliefs of the practitioner and mode of delivery. There was high level of support for caesarean section on maternal request despite the fact that Pakistan‟s caesarean section rate is already high.